HOW SHARIA MICROFINANCE INFLUENCES INFORMAL SECTOR ENTREPRENEURSHIP IN INDONESIA? - Arsyad, Ahmad; Ramadhanty, Rifka Putri; Ryandono, Muhammad Nafik Hadi; Timur, Yan Putra (Airlangga International Journal of Islamic Economics and Finance, 2025)
This study examines the impact of Islamic microfinance on informal businesses in Indonesia, controlling for conventional bank credit, education, population density, and per capita income. Using panel data from 34 provinces (2013–2024) and a Fixed Effects regression model, the analysis shows that Islamic microfinance has a positive but insignificant effect on informal business numbers. Conventional credit also has an insignificant negative effect, while higher education significantly promotes informal entrepreneurship. Population density has a negative but insignificant impact. The findings suggest that education is the key driver of informal sector dynamics, whereas financial access—both Islamic and conventional—faces structural limitations. Strengthening human capital, expanding inclusive financing, and supporting the formalization of informal enterprises are crucial for inclusive development in line with Islamic economic principles. Keywords: Islamic Microfinance, Informal Sector, Education, Population Density